Biomimetic Dehydrogenative Diels–Alder Cycloadditions: Total Syntheses of Brosimones A and B1. Issue 32 (1st July 2013) - Qi, Chao; Cong, Huan; Cahill, Katharine J.; Müller, Peter; Johnson, Richard P.; Porco, John A.
<x xml:space="preserve">Abstract</x> Passing (H2) gas: Concise syntheses of the natural products brosimones A and B have been achieved using sequential dehydrogenative Diels–Alder (DHDA) cycloadditions. The syntheses employ either Pt/C‐cyclopentene or DDQ to effect dehydrogenation of prenylchalcone substrates in combination with silver nanoparticles to promote subsequent Diels–Alder cycloadditions.<boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>